2002
DOI: 10.1038/nbt734
|View full text |Cite
|
Sign up to set email alerts
|

A light-switchable gene promoter system

Abstract: Regulatable transgene systems providing easily controlled, conditional induction or repression of expression are indispensable tools in biomedical and agricultural research and biotechnology. Several such systems have been developed for eukaryotes. Most of these rely on the administration of either exogenous chemicals or heat shock. Despite the general success of many of these systems, the potential for problems, such as toxic, unintended, or pleiotropic effects of the inducing chemical or treatment, can impos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
529
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 565 publications
(536 citation statements)
references
References 19 publications
4
529
2
1
Order By: Relevance
“…2); however, the functional importance of this interaction has yet to be determined (Fujimori et al, 2004). Interestingly, the APB domain of PIF6 and PIF3 along with the N-terminal domain of phyB have been used to develop a light-switchable gene regulatory module for studying cellular signaling pathways in metazoans (Shimizu-Sato et al, 2002;Levskaya et al, 2009;Toettcher et al, 2011aToettcher et al, , 2011bToettcher et al, , 2013.…”
Section: Distinct and Shared Biological Functions Of Pifs In Arabidopsismentioning
confidence: 99%
“…2); however, the functional importance of this interaction has yet to be determined (Fujimori et al, 2004). Interestingly, the APB domain of PIF6 and PIF3 along with the N-terminal domain of phyB have been used to develop a light-switchable gene regulatory module for studying cellular signaling pathways in metazoans (Shimizu-Sato et al, 2002;Levskaya et al, 2009;Toettcher et al, 2011aToettcher et al, , 2011bToettcher et al, , 2013.…”
Section: Distinct and Shared Biological Functions Of Pifs In Arabidopsismentioning
confidence: 99%
“…Recent studies have demonstrated that holo-phytochrome B (holo-PhyB) can be heterologously produced in E. coli through coexpression with two enzymes, heme oxygenase and bilin reductase, that together generate P⌽B from heme (15,16). Similarly, holo-PhyB can be generated in yeast through growth of strains expressing the apo-protein on media containing the phycocyanobilin chromophore (PCB, a close analog of P⌽B) isolated from blue-green algae (17,18). Together, these properties of phytochrome make it an ideal candidate for engineering a reversible, photoswitchable signaling system that combines elements of speed, spatial precision, and reversibility to control the location and timing of protein function.…”
mentioning
confidence: 99%
“…The light switch is based on a molecule (phytochrome in ref. 5) that is synthesized in darkness in the Q1 form. When the Q1 form absorbs a red light photon (wavelength 664 nm) it is transformed into the form Q2.…”
mentioning
confidence: 99%